Retrospective analysis of microbial agents and antibiotic susceptibility patterns in cases of urinary tract infections in domestic canines (2012-2017) - García M., Milagros (2020)
The present study aimed to describe and analyse the results of bacterial isolates and their antibiograms in canine patients with a diagnosis of urinary tract infection, which were treated at the Small Animal Clinic of the Faculty of Veterinary Medicine of Universidad de San Marcos between 2012 and 2017. In total, 97 medical records of patients who had urine cultures and antibiograms exams were identified. The bacterial agents isolated were Escherichia coli (36.9%), Staphylococcus sp (28.7%), Proteus sp (27.9%), Pseudomonas sp (3.3%), Klebsiella sp (1.6%), Streptococcus sp (0.8%) and Citrobacter sp (0.8%) These evidenced a high antibiotic resistance due possibly to the inappropriate use of antibiotics in the country, so it is not possible to recommend a safe initial treatment in canine patients with presumptive diagnosis of this disease.